Litter quality and site characteristics interact to affect the response of priming effect to temperature in subtropical forests. (28th August 2019) - Lyu, Maokui; Nie, Yangyi; Giardina, Christian P.; Vadeboncoeur, Matthew A.; Ren, Yinbang; Fu, Zuoqin; Wang, Minhuang; Jin, Changshan; Liu, Xiuming; Xie, Jinsheng
Abstract: Forest litter inputs to soil can stimulate the decomposition of older soil organic matter (SOM) via a priming effect (PE). The magnitude and underlying mechanisms driving PE are poorly understood, with especially little know about how litter quality and site conditions affect PE in situ. Further, very few studies have examined PE in tropical and subtropical soils. Here, we established low and high elevation sites (600 vs. 1, 400 m a.s.l.) in the subtropical Wuyishan National Park, China, that differed with respect to mean annual temperature (MAT; ∆MAT = 4.2°C), vegetation, soil texture and soil moisture. We conducted a 1‐year field incubation study at these two sites to compare PE induced by adding low‐ and high‐quality 13 C‐labelled leaf litter to soils. At the low elevation site, additions of high‐quality (low C/N) litter caused a PE that was 140% greater than the PE observed following additions of low‐quality (high C/N) litter. In contrast, we saw no significant differences in PE between litter types at the high elevation site, perhaps because PE was not limited by substrate quality at this cooler, finer textured and higher soil moisture coniferous site. In addition, we found a negative relationship between home‐field advantage (HFA) for litter decomposition and PE, indicating that specialized litter decomposer community driving HFA may not accelerate SOM decomposition via PE in the same way. In line with our observed strong relationship between PE and the efficiency of priming (PE size per unit of mineralized litter C), PEs induced by the high‐ and low‐quality litters were directed to microbial phosphorus (P) mining rather than nitrogen (N) mining. This interpretation aligns with observed increases in the activity of P acquiring extracellular enzymes, often described as phosphatases (P‐tases), as well as the positive relationship between the PE, P‐tase activity and the activity of C acquiring extracellular enzymes. Overall, this PE study across two contrasting sites highlights the important role of site characteristics and litter quality in regulating PE size. Further, we suggest that MAT may be a dominant driver of soil priming, through both the direct effects of litter quantity on labile substrate supply and the indirect effects of litter quality changes on downstream decomposer communities. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.